Development of a training package on teaching competencies for mid-level health practitioners - Banas, Alicia Torres
The Mid-level Health Practitioners (MLHP) and other health workers in the health team both in urban and rural community settings have significant roles and responsibilities in improving the health status of the people and eventually improving the people's quality of life. Health education is the most frequent intervention being done by health professionals and other frontline health workers who have direct access to the people. Rendering health service in the form of teaching and health education to individuals, families and aggregates, is to be integrated in almost all the health care services the MLHPs and other health workers rendered. The responsibilities of equipping midwives, volunteer health workers and other community health workers with skills, knowledge and attitudes to become more effective and efficient in teaching/training lies on the MLHPs shoulders. But before the MLHPs can train others to teach and/or train they should be the first to be trained properly and adequately on teaching and/or training. The teaching competencies that they need to acquire in order to teach effectively had to be established first. Then a comprehensive training package on teaching competencies for MLHPs was developed. The overall objective of this project was to develop a training package on teaching competencies for MLHPs. The study was divided into two phases. The first phase generated the experts' opinion on teaching competencies needed by the MLHPs. A five point Likert rating scale was developed with five choice responses: (1) "totally disagree", (2) disagree, (3) "not sure", (4) "agree" and (5) "total agree" to gather consensus of five experts on teaching competencies needed for MLHPs. All the 82 teaching competencies validated by the experts were included in the list of minimum teaching competencies considering that they all registered a mean rating of 4.2 and above. The cut off point indicated at the outset was a mean rating of 4.0. The 82 competency statements validated by the experts were classified into five categories with corresponding number of teaching competencies from highest to lowest: communicating: 25 or 30.48 , planning: 18 or 21.95 , facilitating: 15 or 18.29 , evaluating: 14 or 17.07 , and supervising: 11 or 13.41. Each had a mean rating of 4.2 and above, variable rated from "not sure" to "totally agree". The second phase was the development of a prototype-training package. It involved the formulation of a training design on eight units of instruction based on the competencies established in the first phase of the project. The training package also includes prototype materials. The training designed will run for six days. The units of instruction designed revolved around the five categories: planning, communicating, facilitating, supervising and evaluating. Based on the five categories eight units of instruction were designed. The units are as follows, teaching and learning process, preparation of an instructional plan, appropriate use of instructional media, communication skills and techniques, facilitating small group discussion, different methods of teaching for microteaching, and appropriate use of tools and methods of evaluation. The implementation of this training package on teaching competencies for MLHPs should be highly considered by all clinical instructors in community health nursing, community medicine, training institutions and organizations, and other health professionals who are into community work. The schools/colleges of nursing and medicine and other health professions can adopt these two phases of developing a training package in preparing a teacher training course for health workers assigned in the community setting. The future development of a training package, other methods of data gathering can be tapped like the use of focus group discussion. This training package can also serve as training material for continuing education and faculty/staff development of training institutions or organizations. Likewise, it can also serve as a reference material for further related studies.